Peran Matematika Dalam Agama Islam - Eko Sukaton (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2015)
Mathematics in the public is like to be a difficult thing, so in the minds of most people, mathematics is a subject that is feared. Mathematics associated with storing therein the elements with think logically and correctly where Mathematics guiding people how to think scientifically and should set the path to be able to think his thoughts are true and correct.This is in line with the religion of Islam, where the Islamic religion is taught to think logically, true and correct to the main things to see the greatness of God's creation, and to understand the rules that have been created by God in the Qur'an is loaded with all truth contained therein which aims to the happiness of human life in the world and the hereafter. Regulation is nothing that does not ignore the good of the elements, ie the elements of the good life and eternal happiness, but still ordered to man to act in accordance with the rules of Allah SWT.So the math is not scary lesson to learn but a subject matter that has an important role in the life of the main guiding a keberan Islam. For the learning of mathematics should be encouraged again to make Muslims into people who are able to think logically, based on the right and good way of thinking as it has been taught by math.